PENINGKATAN PENGUASAAN KOSA KATA BAHASA INGGRIS MELALUI METODE PERMAINAN WORD SEARCH GAME DI SISWA KELAS VIII SMPN 4 KOTA TERNATE - Suryani Garwan; Naniek Jusnita (Universitas Khairun, 2020)
The aim of this research is to know the improvement of word search game method that can increase student‘s English vocabulary acquisition. This research was used Classroom Action Research (CAR) which was done in three circles, each circle explained preparation, action, observation and reflection step. Data sources are students, peers, researchers, documents. The results word search game with method steps: (1) prepare a word search game, (2) Game rules, (3) Divide the group, (4) Division of word search game, (5) the time restriction, (6) Doing word search game, (7) Correcting the work, (8) giving evalution, (9) reward. In the assessmen to flearning out comes increased 100%.